La relación entre las dimensiones de los estilos parentales y la alexitimia en adultos jóvenes universitarios de Lima Metropolitana - Bosio Bobadilla, Sabina Beatriz (2023)
The family represents a context in which models of emotional regulation are learned through interaction with caregivers. Therefore, the responsiveness and demandingness patterns that they exercise in the upbringing process will promote to a lesser or greater extent the development of emotional skills in their children. People with alexithymia have difficulties associated with these abilities, which have repercussions on their wellbeing and overall health. Thus, this study analyzes the relationship between the dimensions and sub-dimensions of perceived parental styles and alexithymia in young university adults from Metropolitan Lima. To achieve this, the Perceived Parental Styles Scale (EPPIP) and the Toronto Alexithymia Scale of 20 items (TAS-20) were administered to 232 young adult university students, aged 18–35 years (M = 22.8, SD = 3.15), who belong to public and private universities of Lima Metropolitana, reside in the same city, and were raised by at least one person who took the role of paternal or maternal figure. Positive correlations were found between alexithymia, demandingness, and the subdimensions of indifference, physical coercion, and restrictiveness. Meanwhile, negative correlations were found between alexithymia, responsiveness, and the subdimensions of affection, dialogue, and verbal coercion with alexithymia. In conclusion, having a reference model for emotional management represents a protective factor against alexithymia, while rejection behaviors and parental distance correspond to risk factors for the development of this syndrome. Furthermore, the incorporation of preventive and intervention programs that address these issues, both at an educational and clinical level, is suggested.